2005
DOI: 10.1519/14713.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Field and Laboratory Tests for the Evaluation of Aerobic Capacity in Soccer Players

Abstract: The purpose of this study was to evaluate the maximal oxygen uptake (Vo(2)max) values in soccer players as assessed by field and laboratory tests. Thirty-five elite young soccer players were studied (mean age 18.1 +/- 1.0 years, training duration 8.3 +/- 1.5 years) in the middle of the playing season. All subjects performed 2 maximal field tests: the Yo-Yo endurance test (T(1)) for the estimation of Vo(2)max according to normogram values, and the Yo-Yo intermittent endurance test (T(2)) using portable telemetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 0 publications
3
35
1
5
Order By: Relevance
“…We can consequently conclude that the 20mPST does not provide a solid appraisement of VO 2 max. This result corresponds to Metaxas et al (2005) who, in addition, consider the 20mPST an easy and helpful tool for coaches. The test result, however, should be preferably expressed as distance covered (endurance performance).…”
Section: Discussionsupporting
confidence: 64%
“…We can consequently conclude that the 20mPST does not provide a solid appraisement of VO 2 max. This result corresponds to Metaxas et al (2005) who, in addition, consider the 20mPST an easy and helpful tool for coaches. The test result, however, should be preferably expressed as distance covered (endurance performance).…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have not generally found differences in terms of HRmax measured during the Yo-Yo tests and in different treadmill tests (Stickland et al, 2003; Aziz et al, 2005; Krustrup et al, 2006; Castagna et al, 2006). Metaxas et al (2005) also found no significant differences in HRmax values between the Yo-Yo continuous and intermittent tests as well as 2 maximal exercise treadmill tests with continuous and intermittent protocols. In contrast, we found significant differences between HRmax values measured in the TRT and those measured in each of the Yo-Yo tests.…”
Section: Discussionmentioning
confidence: 69%
“…Computation of YYIE1 test global means, SDs and quantiles (Figure 5) involved 12 studies/subgroups reporting on 770 participants (median age = 21.3 years, IQR = 18.8–44.3 years) (Metaxas et al, 2005; Castagna et al, 2006a; Lategan et al, 2011; Rowan et al, 2012; Deliceoglu, 2013; Mohr et al, 2014; Akashi et al, 2015; Fløtum et al, 2016; Julian et al, 2017; Krustrup et al, 2017; Seidelin et al, 2017). …”
Section: Resultsmentioning
confidence: 99%